Early divorce among Muslim couples in Malaysia : a study of its causes and remedies according to Islamic jurisprudence - Annuur Hakamur Rahimah binti Che Adni (Kulliyyah of Islamic Revealed Knowledge and Human Sciences, International Islamic University Malaysia, 2018)
This research sought to identify the early causes of divorce among Muslim couples in Selangor, Malaysia and remedies according to Islamic jurisprudence. Another primary focus of this research was to analyse the existing measures to remedy the problem. A total of two experts in Islamic jurisprudence were drawn from the Religious Department Islam Selangor (JAIS) and Shah Alam High Court. Thus, a qualitative methodology was selected as the research methodology for analysing the issue. The methodology consists of two aspects: content analysis of the published materials, and in-depth interviews with the relevant experts. The findings indicated the proportion of the population aged 16 and over who were divorced is usually very high in Selangor. The study found that neglect in the responsibility of the spouse was the highest factor recorded as the reason for complaints of divorce cases among spouses in Selangor based on data of the household complaints received and recorded by the Selangor Islamic Religious Department (JAIS) for five years from 2011 to 2015. The usual factors of early divorce are ethical, economic and the social. This research would assert that all these factors are positively correlated with increase of early divorce among Muslims in Selangor. Therefore, the study offers remedies on how to deal with marital problems that occur especially the first five years of marriage. JAIS, as the legal authority which governs Muslim marriage and divorce in Selangor, needs to reevaluate the somewhat outmoded perimeters pertaining to early divorce in order to prevent misunderstanding of JAIS' role in addressing rising divorce rates. In conclusion, the results showed that the three major factors of early divorce directly impact the marriage of the people in Selangor.